2012
DOI: 10.1016/j.jdeveco.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Endogeneity and sample selection in a model for remittances

Abstract: We estimate a remittance model in which we address endogeneity and reverse causality relationships between immigrants' remittances, pre-transfer income and consumption. In order to take into account the fact that a large share of individuals do not remit, instrumental variable variants of the double-hurdle and Heckit selection models are proposed and estimated by Limited Information ML; semiparametric extensions are considered as robustness checks. Our results for a sample of recent immigrants to Australia sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 53 publications
2
50
0
Order By: Relevance
“…This is based on the wisdom of some studies that have shown a complementary relationship between remittance and financial development (e.g. Osabuohien and Efobi, 2012;Bettin et al, 2012;Efobi et al, 2014). These studies points out that in countries with high remittance inflow and improved financial institutions, remittance recipient can better utilise the fund for investment and business development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is based on the wisdom of some studies that have shown a complementary relationship between remittance and financial development (e.g. Osabuohien and Efobi, 2012;Bettin et al, 2012;Efobi et al, 2014). These studies points out that in countries with high remittance inflow and improved financial institutions, remittance recipient can better utilise the fund for investment and business development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If developing countries want to exploit the growth potential of remittances received from their diaspora abroad, the intertemporal behaviour of migrants is a key element in order to predict how these flows might evolve over time. However, as has been convincingly argued in Bettin, Lucchetti, and Zazzaro (2012), an empirical model for remittances must handle properly the endogenous self-selection of remitters. In addition, attention needs to be paid to the potential endogeneity of labour and consumption decisions by households who want to maximize the amounts sent home and set their labour offer and consumption patterns accordingly.…”
Section: Implications For Structural Modelling Of Remittance Behaviourmentioning
confidence: 98%
“…These include the following channels: exchange rate (see Rajan & Subramanian, 2005;Lartey et al, 2008;Acosta et al, 2009;Barajas et al, 2009;Selaya & Thiele, 2010;Dzansi, 2013;Amuedo-Dorantes, 2014) and financial sector development (Aggarwal et al, 2011;Bettin et al, 2012;Osabuohien & Efobi, 2013;Efobi et al, 2014;Kaberuka & Namubiru, 2014;Karikari et al, 2016;Efobi et al, 2016).…”
Section: Stylize Facts Theoretical Underpinnings Intuition and Relamentioning
confidence: 99%